Antimicrobial Activity of CXA-101, a Novel Cephalosporin Tested in Combination with Tazobactam against Enterobacteriaceae, Pseudomonas aeruginosa, and Bacteroides fragilis Strains Having Various Resistance Phenotypes - Sader, Helio S. (American Society for Microbiology, 2011)
CXA-101, a novel oxyimino-aminothiazolyl cephalosporin, CXA-201 (CXA-101 combined with tazobactam), and various comparators were susceptibility tested by broth microdilution methods against 1,301 well-characterized clinical strains collected worldwide, including ceftazidime-resistant members of the family Enterobacteriaceae and Klebsiella pneumoniae carbapenemase (KPC)- and extended-spectrum β-lactamase (ESBL)-producing strains of Pseudomonas aeruginosa and Bacteroides fragilis. CXA-201 was 2- to 32-fold more active than ceftazidime and piperacillin-tazobactam against ceftazidime-resistant Enterobacteriaceae species but less active than cefepime for some species. CXA-101 and CXA-201 were very active against P. aeruginosa (MIC(50), 1 μg/ml for both compounds), including imipenem-resistant strains.